A Study to Assess the Knowledge and Attitude Regarding Substance Use among the Adolescents Residing at Lomeshwar Nagar, Loni (Kd), Maharashtra - Dighe, Sharadchandra V. (Innovational: Journal of Nursing and Healthcare, 2024)
Introduction: Substance use usually begins during adolescence. The causes include poor parental role, peer group influence, low socio-economic status, and media through advertisement of the products. Assessment of knowledge and attitude about substance use is of vital importance for prevention as well as treatment of substance abuse especially in adolescents. Materials and Methods: A cross-sectional survey approach was adapted with a descriptive research design for the study. The data were collected using interview techniques from 60 adolescents who were recruited using simple random sampling method. The data collection tools included Knowledge and attitude questionnaires regarding substance use. Results: The major findings of the study show that 53.33% of the adolescents were in the age group of 12–14 years, 83.33% were male, and 73.33% were from secondary class. 81.66% of the adolescents belong to the Hindu religion, 95% were students and 53.33% were from joint family. About 73.33% of adolescents have heard about substance use. The findings regarding knowledge of substance use show that 53.33% of adolescents have a good level of knowledge. About 91.66% of adolescents have a negative attitude toward the substance use. There was a significant association between knowledge and type of family. There was a mild positive correlation (0.0031) between knowledge and attitude regarding substance use. Conclusion: The study revealed that adolescents have good knowledge and negative attitude towards substance use.